Desulfofrigus sp. prevails in sulfate‐reducing dilution cultures from sediments of the Benguela upwelling area. Issue 1 (4th December 2012) - Kraft, Beate; Engelen, Bert; Goldhammer, Tobias; Lin, Yu‐Shih; Cypionka, Heribert; Könneke, Martin
Abstract: Sediments of coastal upwelling areas are generally characterized by a high content of organic carbon that is mainly degraded via anaerobic microbial processes including sulfate reduction as a major terminal oxidation step. Despite the high importance of sulfate reduction in these sediments, the identity of sulfate‐reducing bacteria (SRB) has remained almost unknown. Here, we applied a cultivation‐based approach using selective enrichment conditions to study the diversity and distribution of active SRB in sediments along a transect perpendicular to the continental slope off the coast of Namibia (Meteor‐cruise M76/1). To promote growth of the most abundant SRB, dilution series were prepared and amended with hydrogen, acetate, or a mixture of monomers representing typical substrates for SRB. Growth of SRB could be detected in the presence of all electron donors and from sediment down to 4 m depth. 16S rRNA gene‐based DGGE analysis and sequencing revealed the predominance of SRB related to psychrophiles in particular to the genus Desulfofrigus, which made up 1 % of the total microbial community, accounting for an absolute abundance of up to 4.8 × 10 7 cells mL −1 . In general, the abundance of cultured SRB changed with depth and between the different sampling sites and correlated with the content of organic carbon as previously reported. Growth of chemolithotrophic SRB in relatively high dilution steps and the enrichment of methanogens as well as acetogens from deeper sediment point to a competition between hydrogen‐utilizing microbial processes and their biogeochemical significance in deep sediment layers of the Benguela upwelling area.